From the inside out : an idiographic account of the policy making process that produced the Irish work place smoking ban - Meaney, Baibre (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2015)
This research goes inside the black box of the civil service policy making world, revealing the processes, procedures, engagements and exchanges that occur when a national policy is being developed, and identifying the challenges relevant to civil service policy makers in the policy making process. This thesis presents is an idiographic account of the policy making process involved in the development of the Irish work place smoking ban. The source of data used in the research is the official record kept by civil servants during the development of this policy, supplemented with key informant interviews. The use of bureaucratic records as a source of data for policy research, and the particular treatments and precautions it's use requires are a key focus in this research. Theoretical concepts of the bureaucratic policy maker and the environment in which she works to produce public policy are explored. The positionality of the researcher is a consideration throughout the research, reflecting the significance of the 'insider' status held.
Keywords: Public Health and Primary Care, Ph.D.; Ph.D. Trinity College Dublin